Periplaneta americana extract ameliorates recurrent oral ulcers in rats by enhancing the intestinal epithelial barrier and regulating gut microbiota - Kailing Li; Liping Yuan; Jingyu Zhang; Weijun Li; Guanhua Zhao; Zhongze Chen; Yongshou Yang; Zhengchun He; Peiyun Xiao (PLoS ONE, 2026)
Background Recurrent oral ulcers (ROUs) of oral mucosa disease are difficult to cure and relapse easily. Periplaneta americana extract (PAD), a raw material used in Kangfuxin Liquid and Yunnan Baiyao toothpaste, contains a variety of growth factors such as polypeptides and sticky sugar amino acids that promote tissue repair; this can encourage the growth of granulation tissue and reduce inflammation on wound surfaces. Objective In this study, we used a rat model of ROU induced by an antigen emulsifier to assess the ameliorative effects of PAD on rat ROUs and to explore its mechanism of action. Methods The effect of PAD in rats was evaluated by an enzyme-linked immunosorbent assay (ELISA) kit, hematoxylin-eosin staining, immunohistochemistry, reverse transcription quantitative PCR (RT-qPCR), and Western Blot (WB). 16S rRNA sequencing and gas chromatography-mass spectrometry (GC-MS) were used to detect the changes in intestinal flora and its metabolite short-chain fatty acids (SCFAs) in the feces of rats, respectively. Results PAD significantly reduced the infiltration of local inflammatory cells and significantly downregulated interleukin (IL)-6 and tumor necrosis factor (TNF-α), while upregulating IL-2, IL-10, and vascular endothelial growth factor (VEGF). In addition, PAD altered the diversity and abundance of the gut microbiota and increased fecal short-chain fatty acid levels. Notably, PAD can improve the pathological injury of the colon, enhance the intestinal barrier of the colon, and reduce the apoptosis of colon cells. Conclusion The oral administration of PAD may effectively treat ROUs via regulating metabolites and altering the composition of the intestinal microbiota, thereby improving the intestinal barrier function.